2007
DOI: 10.4049/jimmunol.179.8.5425
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Innate Immune Defense Mechanisms by Signaling through RIG-I/IPS-1 in Intestinal Epithelial Cells

Abstract: Intestinal epithelial cells (IECs) are a first line of defense against microbial pathogens that enter the host through the intestinal tract. Moreover, viral pathogens that infect the host via the intestinal epithelium are an important cause of morbidity and mortality. However, the mechanisms by which viral pathogens activate antiviral defense mechanisms in IECs are largely unknown. The synthetic dsRNA analog polyinosinic-polycytidylic acid and infection with live virus were used to probe the molecules that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 48 publications
4
57
3
2
Order By: Relevance
“…Response to poly(I-C) and dsRNA could also be mediated by the cytoplasmic viral sensors, the RNA helicases retinoic inducible gene I (RIG-I) and melanoma differentiation-associated gene 5 (MDA-5) (13,28). It was recently reported by Hirata et al that the recognition of poly(I-C) in intestinal epithelial cells is mediated by RIG-I but not by TLR3 (17). The different cell lines used may account for the conflicting findings: whereas, we used the HCT116 cell line, which expresses wild-type p53, Hirata et al utilized cell lines with mutated p53 (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Response to poly(I-C) and dsRNA could also be mediated by the cytoplasmic viral sensors, the RNA helicases retinoic inducible gene I (RIG-I) and melanoma differentiation-associated gene 5 (MDA-5) (13,28). It was recently reported by Hirata et al that the recognition of poly(I-C) in intestinal epithelial cells is mediated by RIG-I but not by TLR3 (17). The different cell lines used may account for the conflicting findings: whereas, we used the HCT116 cell line, which expresses wild-type p53, Hirata et al utilized cell lines with mutated p53 (17).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported by Hirata et al that the recognition of poly(I-C) in intestinal epithelial cells is mediated by RIG-I but not by TLR3 (17). The different cell lines used may account for the conflicting findings: whereas, we used the HCT116 cell line, which expresses wild-type p53, Hirata et al utilized cell lines with mutated p53 (17). We observed that HCT116 p53 ϩ/ϩ and p53 Ϫ/Ϫ cells showed the same expression levels of RIG-I and MDA-5, which indicated that the regulation of their expression might not be dependent on p53 (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Definitive evidence for the role of RIG-I and MDA5 in signaling activated by dsRNA viruses was obtained using mice or cells from mice deficient in either RIG-I or MDA5 (21,30). Using an IEC line (HT-29), we observed that RIG-I was important for the activation of type I IFN production after cells were transfected with the dsRNA analog polyinosinic-polycytidylic acid [poly(I:C)], and this also appeared to be the case when those cells were infected with vesicular stomatitis virus or a strain of rotavirus (31).…”
mentioning
confidence: 98%
“…Transfection of siRNA was performed 24 h prior to transfection of luciferase vectors. Intracellular delivery of poly I:C was performed as previously described (19). Dual luciferase assay was performed using the Dual-Luciferase Reporter Assay System (Promega) and a MicroLumatPlus Luminometer (Berthold Technologies, Bad Wildbad, Germany).…”
Section: Luciferase Assaymentioning
confidence: 99%